Aflatoxins of type B and G affect porcine dendritic cell maturation in vitro. (April 2015) - Mehrzad, Jalil; Devriendt, Bert; Baert, Kim; Cox, Eric
Abstract The toxic effects of highly carcinogenic mycotoxins, especially aflatoxins (AF), on key antigen-presenting cells, such as dendritic cells (DC), are largely unknown. To elucidate the effect of AF on DC function, porcine monocyte-derived DC (MoDC) were treated with a mixture of several AF (i.e., AFB1, AFB2, AFG1, and AFG2) and the phagocytic capacity, the membrane expression level of several DC activation markers, the T-cell proliferation-inducing capacity, and the cytokine secretion pattern were assessed. As compared to untreated MoDC, AF significantly up-regulated the expression of the co-stimulatory molecules CD25 and CD80/86. However, the phagocytic activity of MoDC was not affected by AF treatment. While the cytokine secretion pattern of AF-treated MoDC was similar to control MoDC, the T-cell proliferation-inducing capacity of MoDC was increased upon aflatoxin treatment. The results indicate that a mixture of naturally occurring AF enhances the antigen-presenting capacity of DC, which could explain the observed immunotoxicity of AF by breaking down tolerance and further emphasizes the need to reduce the admissible level of AF in agricultural commodities.